Phenotyping and auto-antibody production by liver-infiltrating B cells in primary sclerosing cholangitis and primary biliary cholangitis. (February 2017) - Chung, Brian K.; Guevel, Bardia T.; Reynolds, Gary M.; Gupta Udatha, D.B.R.K.; Henriksen, Eva Kristine Klemsdal; Stamataki, Zania; Hirschfield, Gideon M.; Karlsen, Tom Hemming; Liaskou, Evaggelia
Abstract: Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are immune-mediated biliary diseases that demonstrate prominent and restricted genetic association with human leukocyte antigen (HLA) alleles. In PBC, anti-mitochondrial antibodies (AMA) are specific and used as diagnostic biomarkers. PSC-relevant auto-antibodies remain controversial despite a distinct HLA association that mirrors archetypical auto-antigen driven disorders. Herein, we compared antibody-secreting B cells (ASCs) in PSC and PBC liver explants to determine if liver-infiltrating ASCs represent an opportune and novel source of disease-relevant auto-antibodies. Using enzymatic digestion and mechanical disruption, liver mononuclear cells (LIMCs) were isolated from fresh PSC and PBC explants and plasmablast (CD19+CD27+CD38 hi CD138−) and plasma cell (CD19+CD27+CD38 hi CD138+) ASCs were enumerated by flow cytometry. We observed 45-fold fewer plasma cells in PSC explants (n = 9) compared to PBC samples (n = 5, p < 0.01) and 10-fold fewer IgA-, IgG- and IgM-positive ASCs (p < 0.05). Liver-infiltrating ASCs from PSC and PBC explants were functional and produced similar concentrations of IgA, IgG and IgM following 2 weeks of culture. Antibody production by PBC ASCs (n = 3) was disease-specific as AMA to pyruvate dehydrogenase complex E2 subunit (PDC-E2) was detected by immunostaining, immunoblotting and ELISA. Antibody profiling of PSC supernatants (n = 9) using full-length recombinant human protein arrays (Cambridge Protein Arrays) revealed reactivities to nucleolar protein 3 (5/9) and hematopoietic cell-specific Lyn substrate 1 (3/9). Array analysis of PBC supernatants (n = 3) detected reactivities to PDC-E2 and hexokinase 1 (3/3). In conclusion, we detected unique frequencies of liver-infiltrating ASCs in PSC and PBC and in so doing, highlight a feasible approach for understanding disease-relevant antibodies in PSC. Highlights: Disease restricted auto-antibody signatures can potentially inform disease pathophysiology. Liver-infiltrating antibody-secreting B cells (ASCs) are reduced in PSC compared to PBC. Cultured liver-infiltrating ASCs in PSC and PBC produce auto-antibodies. Liver-infiltrating ASCs in PBC secrete auto-antibodies to HK1 and PDC-E2. Auto-antibodies from liver-infiltrating ASCs in PSC share reactivity to novel antigen targets.